Healthcare and economic burden of adverse childhood experiences in Lahore, Pakistan - Rehan Shakeel; Muhammed Navid Tahir; Nauman Ali Ch; Assia Riaz (Clinical Epidemiology and Global Health)
Objectives: Strong evidence links ACEs to adverse health outcomes, such as an increased risk of developing many chronic diseases. This study aimed to find the association between exposure to adverse childhood experiences (ACEs) and chronic health diseases and their healthcare and economic burdens in Lahore city. Methods: The Study involved 385 participants from Lahore, Pakistan. Eligible participants who were 18 or older and below 18 years old were excluded. A cross-sectional study was conducted and the sample was collected using a stratified random sampling method. Cross-tabulation and Chi-Square tests were conducted to examine the relationship between exposure to ACEs and the outcomes of chronic diseases. Risk profiles including relative risk, attributable risk, and population attributable risk were calculated to determine the healthcare burden. The economic burden was calculated using DALYs and healthcare costs. Results: The sample had a 59.8 % male predominance, and the average age was 29. 67 % of participants had at least one ACE-related chronic disease such as anxiety, depression, and stroke. A significant association was found between them (p < 0.05). Due to ACEs, study participants lost 1388 years of a healthy life. At the same time, ACE-related healthcare costs were roughly 4200 million PKR (15.14 million USD). Conclusion: The results revealed an elevated risk of chronic health outcomes connected with experiencing one or more ACEs. Addressing ACEs may improve health, reduce healthcare expenditures, and increase resilience.